Kościół na drodze ku „Nostra Aetate”.Zarys relacji chrześcijańsko-żydowskich w XX w. przed II wojną światową - Tulej, Andrzej (Warszawskie Studia Teologiczne, 2018)
A review of the chosen teachings of the Church concerning Jews and Judaism – both official and unofficial – showed that in the twentieth century, before the Second World War, the Church spoke especially in response to the errors of racism, statolatry and various forms of Antisemitism. The historical context were the Russian revolutions, World War I, the fascist movements. The Church's statements intensified when, at the turn of the 1920s and 1930s, the National Socialist Party grew stronger, taking over power in Germany in 1933, leading to the tragedy of World War II and the drama of the Holocaust (Heb. Shoah). Although in its official teachings the Church has always been cautious in wording, in order to avoid direct involvement in political matters or become a party to any conflict, some statements of the popes referring to the broadly understood "Jewish question" can be considered as "milestones". This applies above all to the letter of Pope Benedict XV considered by some to be the most important act of opposition to Antisemitism, the encyclical "Mit brennender Sorge" by Pius XI, opposing the idolatrous relationship to race, nation, state or power and emphasizing the value of the religion of Israel and the Old Testament and the famous formula spoken during the meeting of Pope Pius XI with the Belgian pilgrims: "spiritually, we are all Semites".